2007
DOI: 10.1097/pec.0b013e318159ffef
|View full text |Cite
|
Sign up to set email alerts
|

Resident Exposure to Critical Patients in a Pediatric Emergency Department

Abstract: Pediatric and nonpediatric residents who rotate through a high-volume children's hospital ED are exposed to a very low number of critically ill children. Other educational formats, such as mock resuscitations or standardized patient encounters, may be required to correct this deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 19 publications
3
78
0
Order By: Relevance
“…Our results are similar to those of a PED of a large children's hospital, which found that only 2.5 patients per 1,000 visits required treatment in a resuscitation room. 4 Our data are also consistent with studies that found a low volume of resident exposure to critical illness and resuscitation interventions in the PED, 2,5 as well as the National Registry of Cardiopulmonary Resuscitation, which found that CPR in the PED was exceedingly rare.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results are similar to those of a PED of a large children's hospital, which found that only 2.5 patients per 1,000 visits required treatment in a resuscitation room. 4 Our data are also consistent with studies that found a low volume of resident exposure to critical illness and resuscitation interventions in the PED, 2,5 as well as the National Registry of Cardiopulmonary Resuscitation, which found that CPR in the PED was exceedingly rare.…”
Section: Discussionsupporting
confidence: 81%
“…1 More recently, a study in a large tertiary level PED reported that residents' exposure to critical illness and their opportunities to perform lifesaving interventions were very limited. 2 We found no studies that examined all of the resuscitation interventions performed in a PED.…”
Section: Ré Sumémentioning
confidence: 90%
“…Additionally, Chen et al found that EM residents were more likely to treat older pediatric patients, perform only minor procedures, and see fewer critically ill patients compared to their non-EM peers. 9,10 Similarly, Langhan et al 11 reports that EM residents feel uncomfortable with pediatric and neonatal resuscitations. While we recognize that these individual reports of deficiencies in EM resident education might be attributable to individual systems problems, we believe that collectively they demonstrate the need for a more rigorous core pediatrics curriculum to guide EM resident education.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Studies capturing resident experience have shown gaps in clinical exposure. [4][5][6][7][8][9][10] Many training programs incorporate simulation and online modules to standardize exposure. [11][12][13][14][15][16][17][18][19][20] Web-based modules and lectures can supplement clinical experience, most effectively when used in conjunction with face-to-face instruction.…”
mentioning
confidence: 99%